A Gestalt Theory Approach to Structure in Language - Buffart, Hans; Jacobs, Haike (Frontiers in Psychology, 2021)
The fact that human language is highly structured and that, moreover, the way it is structured shows striking similarities in the world’s languages has been addressed from two different perspectives. The first, and more traditional, generative hypothesis is that the similarities are due to an innate language faculty. There is an inborn ‘grammar’ with universal principles that manifest themselves in each language and cross-linguistic variation arises due to a different parameter setting of universal principles. A second perspective is that there is no inborn, innate language faculty, but that instead structure emerges from language usage. This paper purports to develop and illustrate a third perspective, according to which the structural similarities in human languages are the result of the way the cognitive system works in perception. The essential claim is that structural properties follow from the limitations of human cognition in focus.